The Retention for Young Employees of The Hotel Business (Thailand) - Tangsukeesiri, Preecha; Nonsiri, Petchsri (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The hotel business faces a problem about the young employees resignation which negatively affects the quality of service. Maintaining the new generation of employees with specific behaviors requires appropriate practices that are consistent with the cause of the resignation. The objectives of this research were to study the factors affecting the resignation of the young generation of employees and the method of maintaining the young generation of hotel business in Thailand. The process used the mixed research methodology of quantitative research and qualitative research. The samples in the quantitative research were 500 young generation employees and the qualitative research was an in-depth interview with 10 Human Resource managers (HR) of the hotel business. Data in the questionnaire were analyzed by Exploratory Factor Analysis with Principal Component Analysis and Perpendicular Rotation Axis with Varimax. Qualitative research used content analysis techniques for data analysis. The study found three factors affecting the resignation of young generation of employees. First, they lack patience. Second, they have high self-confidence, and third, they aspire for professional growth. With regard to the method of maintaining the young generation of hotel business employees, the results of the study suggest that in the following are important : consultation, teamwork, healthy working environment and conduct, training and challenging assignments.